Menumbuh Kembangkan Jiwa Kewirausahaan Santri Dengan Produksi Jilbab dan Masker Secara Mandiri di Pesantren Ulumul Qur’an Stabat - Husni Thamrin; Agus Suriadi; Munzaimah Masril (Pelita Masyarakat, 2022)
The program fosters the entrepreneurial spirit in all levels of society, becoming an important thing that must be done to overcome and anticipate the development of the hususnya era in the conditions of the covid-19 pandemic. Entrepreneurship training becomes one solution as an effort to foster the entrepreneurial spirit in the community. The methods carried out in this program are Socialization to grow the entrepreneurial spirit, Training in Making hijabs and masks, Training in Organizational Management and Marketing and Providing production support assistance.  Pondok pesantren is one of the nor formal educational institutions in Indonesia, which serves as a source of value and morality, to print qualified cadres and experts in the field of religion. But it is inevitable the fact that santri individuals come from different backgrounds and have different interests and talents. With its distinctive culture, the combination of santri and pesantren culture can produce entrepreneurs in the field of creative enterprises that can produce various pruduk for economic independence in pesantren. Partners in community service with this Community Partnership Program scheme are Para santri at pondok ulumul Quran Jalan Wahid Hasyim, Kwala Bingai, Stabat, Langkat Regency, North Sumatra.